2016
DOI: 10.3892/ol.2016.5483
|View full text |Cite
|
Sign up to set email alerts
|

Primary breast lymphoma: A single center study

Abstract: Abstract. The aim of the present study was to summarize the clinical characteristics of primary breast lymphoma (PBL) and evaluate its management approaches. A total of 29 patients newly diagnosed with PBL, and treated between April 2006 and May 2013, were analyzed retrospectively. The median survival follow-up time for all patients was 66.8 (range, 25.4-110.0) months. The results of the follow-up revealed 22 living lymphoma-free patients and 7 patients who had succumbed to PBL. Of the 7 deceased patients, 6 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…A recently published phase III study reported there was no statistically difference in the event-free survival (EFS) rate, and the OS rate after patients with DLBCL received rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R+CHOP) chemotherapy combined with radiotherapy or non-combined radiotherapy [24], which demonstrated that radiotherapy did not improve patient prognosis. Studies have shown that the use of radiotherapy did not improve the OS in patients with primary lymphoma of the breast [25,26]. However, several studies have shown that although the use of radiotherapy did not improve the OS of patients with primary DLBCL of the breast, the use of chemotherapy combined with radiotherapy could reduce local recurrence [11,27].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published phase III study reported there was no statistically difference in the event-free survival (EFS) rate, and the OS rate after patients with DLBCL received rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R+CHOP) chemotherapy combined with radiotherapy or non-combined radiotherapy [24], which demonstrated that radiotherapy did not improve patient prognosis. Studies have shown that the use of radiotherapy did not improve the OS in patients with primary lymphoma of the breast [25,26]. However, several studies have shown that although the use of radiotherapy did not improve the OS of patients with primary DLBCL of the breast, the use of chemotherapy combined with radiotherapy could reduce local recurrence [11,27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, methods for the early diagnosis, accurate prediction, and appropriate treatment of breast cancer still need to be developed. Understanding the molecular pathways involved in the pathogenesis of breast cancer is necessary to maximize treatment efficiency 4…”
Section: Introductionmentioning
confidence: 99%
“… 3 Although advances in early diagnosis, surgery, chemotherapy, and other treatment methods have greatly improved the prognosis of BC patients, the survival of them is still not optimistic due to the high heterogeneity of BC cells and the increasing resistance of tumor cells to chemotherapeutic drugs. 4 Therefore, the call for understanding the mechanism of BC development and the development of drug resistance, and finding more targets for treating BC is overwhelmingly urgent.…”
Section: Introductionmentioning
confidence: 99%